2018
DOI: 10.1093/intqhc/mzy035
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement project to increase self-administration of medicines in an acute hospital

Abstract: Quality problem or issueA patient survey found significantly fewer patients reported they had self-administered their medicines while in hospital (20% of 100 patients) than reported that they would like to (44% of 100). We aimed to make self-administration more easily available to patients who wanted it.Initial assessmentWe conducted a failure, modes and effects analysis, collected baseline data on four wards and carried out observations.Choice of solutionOur initial assessment suggested that the main areas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In comparison with nurse-administered medication, self-administered medication (SAM) reduces omitted dosing and medication errors in hospitals and increases patient medication knowledge, adherence, and satisfaction; therefore, it has been encouraged in many hospitals worldwide. [2][3][4][5] Patient's self-administration could save 70 minutes/day for nurses to spend their time in informing patients on their medication. 6 Despite evidence on benefits, SAM implementation among in-patient service has still been limited, including in Thailand.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison with nurse-administered medication, self-administered medication (SAM) reduces omitted dosing and medication errors in hospitals and increases patient medication knowledge, adherence, and satisfaction; therefore, it has been encouraged in many hospitals worldwide. [2][3][4][5] Patient's self-administration could save 70 minutes/day for nurses to spend their time in informing patients on their medication. 6 Despite evidence on benefits, SAM implementation among in-patient service has still been limited, including in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite evidence on benefits, SAM implementation among in-patient service has still been limited, including in Thailand. 4,[7][8][9] It was, therefore, not surprising that patients were lacking knowledge on medication side effects and on how to take medication after hospital discharge which could lead to non-adherence, drug related problems, or readmission. 3,[10][11][12] A study conducted phone interview within 48 hours after discharge from a medical ward reported that only 43% of patients could specify the name of all medications received and 36% could specify the indications of the prescribed medications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of adopting a structured risk assessment for enhancing care of patients is discussed in literature. Several methods for structuring the risk assessment process, are discussed, for example, the Healthcare Failure Mode and Effect Analysis (HFMEA) (McElroy et al 2016;Franklin et al 2012;Rosen et al 2015;Garfield et al 2018;De Giorgi et al 2010), Preliminary hazard analysis (PHA) (Schlatter 2018;Riou et al 2017;Grespan et al 2019Grespan et al , 2007De Giorgi et al 2010), and the Fault Tree Analysis (FTA) (McElroy et al 2017;Rogith et al 2017;Teixeira et al 2016;Ong and Coiera 2010). Nonetheless, owing to the uncertain nature of risks embedded in the clinical care pathways, applying specific risk assessment methods is not straightforward because of factors such as the need for patient records (for quantitative methods), domain knowledge, or user-knowledge on using different methods while assessing risks (Chemweno et al 2018;Beaussier et al 2016;Paine et al 2018).…”
Section: Introductionmentioning
confidence: 99%